A study of the role of calcium and oxidative stress in pathophysiology of osteoporosis in postmenopausal women-a review - Haddig, Nour El-Houda; Zerzour, Aicha; Derouiche, Samir (Yayasan Ahmar Cendekia Indonesia, 2020)
The aim of this review was to identify the role of calcium and oxidative stress as factors associated with osteoporosis in postmenopausal women. There are many diseases related to post-menstruation in women, the most important of which is osteoporosis. Calcium levels remains stable until menopause, when the bone resorption rate increases in association with the decrease in ovarian estrogen production that effect the intestinal calcium absorption. On the other hand, studies support that oxidative stress is directly involved in the genesis and development of osteoporosis. However, Oxidative stress blocks the activation of osteoblasts and activates the differentiation of osteoclasts which led to increased resorption rate without adequate and proper bone formation. In conclusion, Physiological changes in postmenopausal women lead to fluctuations in calcium metabolism and oxidative stress, which may lead to the occurrence or development of osteoporosis.